ANALISIS PENATAUSAHAAN KEUANGAN DAERAH PADA BIRO KESEJAHTERAAN SOSIAL SEKRETARIAT DAERAH PROVINSI KALIMANTAN BARAT - B51107109, Putri Damayanti (Jurnal KIAFE, 2013)
The title of the study is the analysis of the Regional Financial Control Administration of Biro Kesejahteraan Sosial Sekretariat Daerah of West Kalimantan Province. Background research that every Local Government Unit that controls the documents related to the state treasury are required to administer and maintain the documents properly in accordance with applicable regulations. This is also true in the Biro Kesejahteraan Sosial Sekretariat Daerah of West Kalimantan Province who perform local financial administration by appointing a financial management officer, with the financial administration hopes can be held in an orderly, good order and discipline in the administration of the distribution of the budget in accordance with a predetermined plan. Be limited to the first research problems, whether financial administration of local control by the Minister of Home Affairs Regulation No. 13 of 2006, the Minister of Home Affairs Regulation No. 59 of 2007 and the Minister of Home Affairs Regulation No. 21 of 2011 has been adequately implemented at the Biro Kesejahteraan Sosial Sekretariat Daerah of West Kalimantan Province ?. Secondly, whether the inhibiting factors in the control of local financial administration by the Minister of Home Affairs Number 13 Year 2006, the Minister of Home Affairs Number 59 Year 2007 and the Regulation of the Minister of Home Affairs Number 21 Year 2011. The first study objective was to determine the financial administration control area by the Minister of Home Affairs No. 13 of 2006, Regulation of the Minister of Home Affairs No. 59 of 2007 and the Regulation of the Minister of Home Affairs No. 21 of 2011 which was held at the Biro Kesejahteraan Sosial Sekretariat Daerah of West Kalimantan Province. Second, to determine the limiting factors in the control of local financial administration by the Minister of Home Affairs Regulation No. 13 of 2006, the Minister of Home Affairs Regulation No. 59 of 2007 and the Minister of Home Affairs. Regulation No. 21 of 2011. The method used is descriptive method is a method for describing the solution to the problem of the study, with the form of case study research. Data processing techniques using descriptive analysis and evaluation of internal control questionnaires. From the analysis of the financial administration control areas on the Biro Kesejahteraan Sosial Sekretariat Daerah of West Kalimantan Province is not in accordance with the Regulation of the Minister of Home Affairs No. 13 of 2006, the Minister of Home Affairs Regulation No. 59 of 2007 and the Minister of Home Affairs Regulation No. 21 of 2011. It can be seen from the administration of systems and procedures that have been implemented. Results Internal Control Qusioner neighbor control spending money of 65.48 per cent and by 73 per cent control of the organization. Thus the implementation of the financial administration in the area of Biro Kesejahteraan Sosial Sekretariat Daerah of West Kalimantan Province has not been effective or adequate. Inhibiting factors in the control of local financial administration by the Minister of Home Affairs Regulation No. 13 of 2006, the Minister of Home Affairs Regulation No. 59 of 2007 and the Minister of Home Affairs Regulation No. 21 of 2011, among others, not all of the financial management officer who understands the powers and duties that should be responsibilities, human resources are still limited, especially employees who have knowledge and skills in particular accounting and governmental accounting and financial information systems area not optimal checking the documents with the accounting records so that the lack of accountability of the financial statements of the regional work units. Key : Analysis of the Regional Financial Control Administration, financial management officer, internal control